Effect of Pre-Treatment Processes and Packaging on Puffing Quality of Microwavable Puffed Pork Rinds (Kab-Moo) - Bunthawong, Orathai; Khamkruea, Nichapha (Journal of Food Technology, Siam University, 2021)
This research was aimed at investigating pre-treatment processes and package type for microwavable puffed pork rinds (Kab-Moo). Boiling time of pork rinds in oil were studied (2-6 hours), length of instant pork rind (1-3 centimeters), microwave power out put (700 and 900 watts), microwavable packaging types (paper bag, plastic bag and plastic box) and packing weight (14-22 grams) were carried out. The optimum of process was boiling the pork rind product of 3 centimeters long for 5 hours 30 minutes. As the boiling time increased, moisture content of pork rinds trended to decline. While the expansion ratio increased, hardness tended to decline. The microwave puffed pork rind from different of packaging type and packing weight had expansion ratio and hardness were significant difference (p≤0.05). Pork rinds with packing weight of 16-18 grams could be puffed in paper bag, plastic bag and plastic box by microwave oven at 700 watts. The puffing quality (expansion ratio and hardness) of products from aforementioned conditions were not significant difference (p>0.05).